2013
DOI: 10.1590/s1413-81232013000900031
|View full text |Cite
|
Sign up to set email alerts
|

Atitude frente à morte em profissionais e estudantes de enfermagem: revisão da produção científica da última década

Abstract: Atitude frente à morte em profissionais e estudantes de enfermagem: revisão da produção científica da última décadaThe attitude among nursing professionals and students when facing death: a review of the scientific literature of the last decade

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
53

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(85 citation statements)
references
References 30 publications
1
31
0
53
Order By: Relevance
“…[7][8]18 As evidenced in the present study, 758 (75.4%) students did not participate in any discussion on the subject of death and dying during the undergraduate course, which may impact the way care is performed. 10,13,[17][18] A literature review 18 clarifies the need for professional training on the subject of death and dying, as well as previous training programs from the beginning of professional practice as part of the education of nurses A study performed with two different groups of nurses observed that, after a group received training on the subject of death, the attitudes towards the death of these nurses became positive, while the other group, who did not have access to the same training, did not obtain significant changes. 19 Those educated about death and dying are better able to care for people who are dying.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8]18 As evidenced in the present study, 758 (75.4%) students did not participate in any discussion on the subject of death and dying during the undergraduate course, which may impact the way care is performed. 10,13,[17][18] A literature review 18 clarifies the need for professional training on the subject of death and dying, as well as previous training programs from the beginning of professional practice as part of the education of nurses A study performed with two different groups of nurses observed that, after a group received training on the subject of death, the attitudes towards the death of these nurses became positive, while the other group, who did not have access to the same training, did not obtain significant changes. 19 Those educated about death and dying are better able to care for people who are dying.…”
Section: Discussionmentioning
confidence: 99%
“…Implementing health services aimed at professionals can also ensure better preparedness and ability to cope with the process of losing a patient 27 . Albuquerque 28 reinforces this perspective when pointing out that, in order to humanize health care, professionals must also be considered, taking into account the needs arising from the professional practice itself.…”
Section: Challenges Of Home Care For Terminal Patientsmentioning
confidence: 99%
“…Embora a enfermagem seja uma das profissões de saúde mais suscetível ao estresse laboral devido ao contato direto, intenso e prolongado com o paciente, em especial na terapia intensiva, essas demandas exigiram menor atenção do enfermeiro. Falar sobre morte e a convivência com essa condição no processo de trabalho do enfermeiro em terapia intensiva pode ser apontado como evento esperado em virtude da condição clínica dos pacientes e ser considerada como transição e processo natural relacionado ao ciclo vital humano (19) . Por outro lado, a morte pode ser revelada como processo difícil que envolve sofrimento e desgaste emocional desse profissional ou ainda traduzir-se em conhecimento limitado para lidar com o mesmo, pois sua formação é voltada às ações técnicas e práticas e pouco embasamento sobre o campo das necessidades de pacientes e famílias em processo de finitude (20) .…”
Section: As Situações De Demandas Que Mais Exigiram Atenção Dos Enferunclassified